Penerapan Model Kooperatif Tipe TGT Untuk Meningkatkan Motivasi Dan Prestasi Belajar Siswa Kelas V SD - Walanty, Putri (Universitas Bengkulu, 2024)
This study aims to increase the motivation and learning achievement of VD class students at SDN 77 Bengkulu City by applying the cooperative learning model of the Teams Games Tournament type. This research is a Classroom Action Research. The subjects of this study were 16 male students and 18 female students. There are two research instruments that will be used by researchers in this study, namely the observation sheet and the test. In the first cycle, 10 students got good and very good criteria for learning motivation with a percentage of 29.4%. In cycle II, students' motivation to get good and very good criteria was 33 people with a percentage of 97.05%. In the aspect of student achievement, the increase from the first cycle of IPS subjects was 69.93 to 83.82 with classical completeness of 61.76% to 85.29% in the second cycle. Indonesian subjects from cycle I 71.10 to 83.68 with classical completeness 58.82% to 91.18% in cycle II. Thus the application of the Teams Games Tournament cooperative learning model can increase motivation and student learning achievement in thematic learning in class VD SDN 77 Bengkulu City.